Mapping Recorded Homicide in Indonesia: An Ecological Criminological Analysis Using BPS Data - Zul Khaidir Kadir (Punggawa Law Review, 2026)
This article maps recorded homicide in Indonesia using BPS-based crime statistics and interprets its territorial visibility through ecological criminology. Rather than treating homicide only as an individual criminal act or as a doctrinal problem of criminal law, the article examines how officially recorded lethal violence appears across national, provincial, village-level, and police-region data. The study uses a descriptive ecological criminological design based on Statistik Kriminal 2024/2025. The findings show that recorded homicide declined slightly from 1,129 incidents in 2023 to 1,106 incidents in 2024. Podes-based territorial data show that the percentage of villages or urban villages with homicide incidents in 2024 ranged from 0.18 percent to 1.87 percent, with the highest percentages in DKI Jakarta, Papua Selatan, and Papua Tengah, and the lowest in Aceh, Kalimantan Utara, and Bali. As a supporting comparison, police-region data on crimes against life show the highest burden in Jawa Timur, Sumatera Utara, and Papua. The article argues that these data should be interpreted as indicators of official visibility and territorial burden, not as direct measures of individual criminality or causal explanation. By linking BPS data with ecological criminological theory, the article contributes to Indonesian homicide studies by offering a disciplined descriptive mapping of recorded homicide while clarifying the methodological limits of official statistics.